2008
DOI: 10.1159/000130417
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Treatment-Resistant Heroin Addicts with and without DSM-IV Axis 1 Psychiatric Comorbidity (Dual Diagnosis)

Abstract: Objective: The aim of this study was to compare the long-term outcomes of treatment-resistant heroin addicts with and without DSM-IV axis I psychiatric comorbidity (dual diagnosis). Method: 129 heroin addicts who also met criteria for treatment resistance, 66 with one or more DSM-IV axis I psychiatric diagnosis (DD patients), and 63 without DSM-IV axis I psychiatric comorbidity (NDD patients) were monitored prospectively (6 years on average, min. 1, max. 9) along a methadone maintenance treatment program (MMTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 60 publications
6
22
1
1
Order By: Relevance
“…Conversely, our results are consistent with those obtained in longitudinal studies carried out on methadonemaintained opioid addict populations [19,20,23,24,40] . Specifically, our findings on retention in treatment are consistent with those obtained in a previous retrospective study in which psychiatric severity was established on the basis of the referral of patients to a consultant psychiatrist [20] , and in other studies discriminating patients on the basis of formal psychiatric diagnosis [21][22][23][24] .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Conversely, our results are consistent with those obtained in longitudinal studies carried out on methadonemaintained opioid addict populations [19,20,23,24,40] . Specifically, our findings on retention in treatment are consistent with those obtained in a previous retrospective study in which psychiatric severity was established on the basis of the referral of patients to a consultant psychiatrist [20] , and in other studies discriminating patients on the basis of formal psychiatric diagnosis [21][22][23][24] .…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, our findings on retention in treatment are consistent with those obtained in a previous retrospective study in which psychiatric severity was established on the basis of the referral of patients to a consultant psychiatrist [20] , and in other studies discriminating patients on the basis of formal psychiatric diagnosis [21][22][23][24] . These studies found no statistically significant difference between patients with and without psychiatric comorbidity, at times revealing an even higher retention rate for patients with psychiatric comorbidity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The last 2 variables also predicted longer retention and no opioid and benzodiazepine abuse, among others. In this study, no psychiatric diagnosis was a positive predictor, while Maremmani et al [45,46] found the opposite result. A 4.5 years' prospective study in Macao also showed a high long-term retention of patients in opioid maintenance therapy [47].…”
Section: Discussioncontrasting
confidence: 49%